The teaching of mathematics in EJA: The limits and challenges in pedagogical practice - Junior, Gean Pereira Silva; Pagoto, Leticia Martelo; Pagoto, Jaine Martelo; Bispo, Rodrigo Andraus; Moraes, Maria Paula Hêngling Christófani; Fazzan, João Victor; Pereira, Adriana Maria; Rossi, Carlos Henrique; Antoniali, Natalia; Ochiussi, Daiane Simiele (Seven Editora, 2024)
This study addresses Adult and Youth Education (AYE) as a form of education aimed at social inclusion and the comprehensive development of individuals who did not complete their basic education at the appropriate age. AYE faces challenges such as school dropout rates and lack of resources, necessitating the strengthening of educational policies in this area. The aim of this study is to analyze the challenges and opportunities of AYE in the development of literacy, with a focus on mathematics education, through a literature review. The methodology involved a comprehensive literature review, seeking theoretical and conceptual insights. The role of the teacher in AYE is emphasized, with a focus on the importance of the affective aspect in learning. The paper also discusses literacy and numeracy, highlighting their relationship and relevance in education. Mathematical literacy is introduced as fundamental for understanding everyday situations. DOI:https://doi.org/10.56238/sevened2024.010-052